The Issues of Pancasila and Citizenship Education Learning Practices in Indonesia - Saraswati, Dewi; Yani, Muhammad Turhan; Hermanto, Hermanto (Universitas Negeri Padang, 2024)
In practice, Pancasila and Citizenship education has a large role in shaping the character of students in Indonesia. However, in its implementation problems are often found that need to be resolved seriously in order to increase the effectiveness of learning. Due to the various problems above, researchers feel the need to research more deeply into the Problems of Educational Learning Practices. The aim of this research is to find out direct problems in the field using literature studies in Indonesia so that these problems can find the right solution to improve the quality and relevance of education. . This research was obtained from literature observations through national article findings. The scope of this research study is in the form of problems found in the implementation of Pancasila and Citizenship Education learning in various regions in Indonesia. This research produced findings in the form of 4 problematic topics in learning Pancasila and Citizenship Education, namely Learning Materials, Learning Methods, Teacher and Student Readiness.